Analysis of scientific production on women entrepreneurs in conflict zones - Sánchez Castillo, Verenice; Gómez Cano, Carlos Alberto (Data and Metadata, 2025)
This article presents a bibliometric analysis of the scientific production about women entrepreneurs in conflict zones, to identify trends, gaps, and areas of opportunity in research on this topic. Through a methodological approach based on seven dimensions and a continuous disaggregation process, the evolution of the field and its impact in contexts affected by violence were examined. The results showed a significant growth in academic production during the last decade, with an interdisciplinary approach that integrates gender, economic, and human rights perspectives. International collaboration networks were identified, as well as the predominance of topics such as economic empowerment, gender violence, and resilience in post-conflict contexts. However, gaps were observed in the representation and practical application of academic findings in public policies. The study presents lines to strengthen research, foster global collaboration, generate new knowledge, and base concrete actions that promote female entrepreneurship as a tool for social transformation in conflict zones.